The Role of the Constitutional Court in Protecting Human Rights (HAM) in Indonesia - Muhammad Alvin Sandjaya; Asep Suherman (JUSTICES: Journal of Law, 2025)
The Constitutional Court (MK) has an important role as the final interpreter of the constitution and protector of human rights (HAM) in Indonesia. The Constitutional Court is tasked with examining the constitutionality of laws, ensuring the conformity of regulations with the 1945 Constitution, and protecting individual rights through decisions that confirm the basic rights of citizens. The Constitutional Court also plays a role in resolving general election disputes to maintain the integrity of democracy. The Constitutional Court's important decisions, such as freedom of expression, protection of minority rights, and the right to legal protection in detention, demonstrate this institution's commitment to upholding human rights. However, challenges in implementing MK decisions include low public legal awareness, complicated bureaucratic procedures, and resistance from parties with certain interests. The success of upholding human rights depends on political commitment, support from relevant institutions, and public acceptance of the necessary changes.